Food culture : anthropology, linguistics and food studies - Chrzan, Janet; Brett, John A. (Research methods for anthropological studies of food and nutrition, 2017)
This volume offers a comprehensive guide to methods used in the sociocultural, linguistic and historical research of food use. This volume is unique in offering food-related research methods from multiple academic disciplines, and includes methods that bridge disciplines to provide a thorough review of best practices. In each chapter, a case study from the author's own work is to illustrate why the methods were adopted in that particular case along with abundant additional resources to further develop and explore the methods.